Thymus algeriensis and Artemisia herba-alba Essential Oils: Chemical Analysis, Antioxidant Potential and In Vivo Anti-Inflammatory, Analgesic Activities, and Acute Toxicity - Khadija El Ouahdani (MDPI AG, 2021)
The study of bioactive molecules of natural origin is a focus of current research. Thymus algeriensis and Artemisia herba-alba are two medicinal plants widely used by the Moroccan population in the traditional treatment of several pathologies linked to inflammation. This study aimed to evaluate the single and combined antioxidant, anti-inflammatory and analgesic effects of the essential oils extracted from these two medicinal plants, and also their potential toxicity. Essential oils were extracted using hydro-distillation in a Clevenger-type apparatus. The antioxidant activity was evaluated by two methods: the scavenging of the free radical DPPH, and the reduction in iron. Anti-inflammatory activity was evaluated by evaluating the edema development induced by carrageenan injecting, while the analgesic power was evaluated according to the number of abdominal contortions induced by the intraperitoneal injection of acetic acid (0.7%). The acute oral toxicity was performed to assess the potential toxicity of the studied EOs, followed by an analysis of the blood biochemical parameters. The results of the two antioxidant tests indicated that our extract mixture exhibits good iron reduction capacity and very interesting DPPH free radical scavenging power, with an IC50 of around 4.38 ± 0.98 μg/mL higher than that of the benchmark antioxidant, BHT. The anti-inflammatory test demonstrated that the mixture administered orally at a dose of 150 mg/kg has a better activity, exceeding that of 1% Diclofenac, with a percentage of maximum inhibition of the edema of 89.99 ± 4.08. The number of cramps in the mice treated with the mixture at a dose of 150 mg/kg is significantly lower (29.80 ± 1.92) than those of the group treated with Tramadol (42.00 ± 2.70), respectively. The toxicity results show no signs of toxicity with an LD50 greater than 150 mg/Kg. These interesting results show that the two plants’ EOs had an important anti-inflammatory, analgesic, and antioxidant activity, and also a powerful synergistic effect, which encourages further in-depth investigations on their pharmacological proprieties.